2016
DOI: 10.1186/s40813-016-0047-9
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against parasites – status quo and the way forward

Abstract: Although vaccination against various pathogens is integral to health management of swine, vaccines against parasites have not yet been commercialized for the use in pigs. The incentive to develop and commercialize anti-parasitic vaccines in swine are twofold; on the one hand parasitic diseases which are economically important, such as ascarosis and neonatal coccidiosis, could be controlled in a sustainable manner; on the other hand, the transmission of zoonotic parasites, such as Toxoplasma gondii or Cysticerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In the past decade, significant progress has been made in the development of T. gondii vaccines, new antigens, adjuvants, and immunization strategies. Vaccine candidates range from attenuated vaccines, subunit vaccines, DNAs, RNAs, and exosomes ( 17 , 18 ) The advantages and disadvantages of these vaccines have been studied primarily in mouse models to determine their potential to elicit cellular and humoral immune responses and their protective effects against T. gondii challenge ( 19 22 ). The main disadvantage of these vaccine models is that the great majority of them was not able to protect against the virulent challenge ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, significant progress has been made in the development of T. gondii vaccines, new antigens, adjuvants, and immunization strategies. Vaccine candidates range from attenuated vaccines, subunit vaccines, DNAs, RNAs, and exosomes ( 17 , 18 ) The advantages and disadvantages of these vaccines have been studied primarily in mouse models to determine their potential to elicit cellular and humoral immune responses and their protective effects against T. gondii challenge ( 19 22 ). The main disadvantage of these vaccine models is that the great majority of them was not able to protect against the virulent challenge ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, vaccines would lessen the need for antibiotics to control diseases and offer veterinary practitioners much needed tools (Potter et al, 2008 ; Kolotilin et al, 2014 ). Moreover, the growing public interest in production of chemical-free food, which is fostered by consumer concern about drug residues in meat, eggs or milk supports the importance of the development of new veterinary vaccines (Murphy, 2012 ; Joachim, 2016 ).…”
Section: Veterinary Vaccine Development Against Fbds Caused By Parasimentioning
confidence: 99%
“…For example, vaccines provide long-term protection and eliminate the phenomenon of drug resistance of T. spiralis . Moreover, vaccines improve food safety by reducing drug residues in meat ( Joachim, 2016 ; Sander et al, 2020 ). Studies have found that a window period between T. spiralis infection and anti- Trichinella IgG positivity ( Gamble et al, 2004 ; Cui J. et al, 2015 ; Wang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%